The pituitary-gonadal-thyroid and lactotroph axes in critically ill patients - (:unkn) unknown (VIA MEDICA, 2016)
Introduction: The normal circadian rhythm of hormones in critical patients becomes chaotic causing some hormones to increase and others to decrease abnormally. The goal of this study is to evaluate hormonal changes in severely ill patients and to investigate the relationship between hormonal changes and mortality and morbidity. Material and methods: We enrolled 20 patients (10 F/10 M). Blood samples were collected on day 0, day 5, and day 10. If a patient was discharged before these defined days, a sample was drawn on that day. Twenty healthy controls were included. Results: Female patients had lower LH, FSH, and fT(3) and higher PRL and cortisol levels than controls on admission to the intensive care unit (ICU) (p(LH) = 0.021, p(FsH):0.001, p(f13) = 0.021, p(PRL) = 0.042, p(Cortisol) < 0.001, respectively). Men had significantly low testosterone and fT(3), and high PRL and cortisol levels on ICU admission (p(T) = 0.01, p(fT3) = 0.043, p(PRL) = 0.005, p(Cortisol) < 0.001, respectively). The lowest levels of gonadotropins in both genders and testosterone in men were measured on day 5. Cortisol levels decreased in the patients discharged from the ICU (p = 0.01). FSH levels increased in recovered women (p(FSH) = 0.043). The mortality rate was 30%. There were correlations between admission TSH and NIMV duration (p = 0.006), fT(3) and APACHE II (p = 0.001), and PRL and mortality (p = 0.044). Positive correlations between E-2 and APACHE II (p = 0.003) in females, and PRL and APACHE II (p = 0.022) in males were also displayed. Conclusions: Critically ill patients develop significant changes in neuroendocrine axes. Alterations in hormones correlate with the disease severity and mortality.
Keywords: mortality; neuroendocrine changes; prolactin; severe illness; NONTHYROIDAL ILLNESS SYNDROME; PROLONGED CRITICAL ILLNESS; INTENSIVE-CARE-UNIT; GONADOTROPIN-SECRETION; POSTMENOPAUSAL FEMALE; AXIS; MEN; HYPOGONADISM; DISEASE; STEROIDOGENESIS